On legal geography as an analytical toolbox for EU legal studies. Issue 1 (March 2022) - Persdotter, Maria; Iossa, Andrea
Abstract: EU legal geography concerns itself with the mutually constitutive relationship between EU law and space (also, and increasingly so, time). This requires reconstructing and systematizing the widely used concepts which reveal the geographical basis of EU law (such as movement and circulation), but also developing a particular viewpoint, indeed a specific "ethos of investigation", which equips us with the tools to challenge and transcend the dominant ways of doing EU law. In particular, it is argued that a geographic turn in European legal studies will foster the study of how law works "on the ground" and will allow challenging taken-for-granted ideas about the relationship between law and political order, while throwing new light on the very technical concepts with which we reconstruct, analyse and assess EU law.